Pseudo-Duane’s retraction syndrome: a rare clinical entity - Chandran, Sobhana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Studies of sequelae of isolated medial orbital wall fractures show that the majority of patients with this condition are often asymptomatic, which makes the diagnosis based only on clinical grounds difficult. One of the rare complications of this entity is Pseudo-Duane’s retraction syndrome, which is characterised by horizontal diplopia, restricted abduction with or without limited adduction, accompanied by narrowing of the palpebral fissure, globe retraction and pseudo ptosis on abduction. This is a case report of a 46-year-old female who developed Pseudo-Duane’s retraction syndrome following trauma to her left orbit. She presented with left eye pain, diplopia, horizontal gaze restrictions, left eye ecchymosis and enophthalmos. Careful history taking and thorough ophthalmic examination including forced duction test along with radiological imaging helped clinch this diagnosis. Timely intervention by an endoscopic approach to release the medial rectus muscle entrapped within the fracture resolved the patient’s symptoms.